Penggunaan Minyak Zaitun untuk Mencegah Perburukan Luka Tekan pada Pasien Intensive Care Unit: Seri Kasus Deskriptif - Angga Sri Hidayana; Dwi Nur Rahmantika Puji Safitri; Khoiriyah Khoiriyah (Tribhuwana Tunggadewi University, 2026)
Pressure ulcers are a common complication in patients admitted to the Intensive Care Unit (ICU) due to immobility and decreased level of consciousness. Olive oil contains essential fatty acids that have the potential to help maintain skin integrity and can therefore be used as part of nursing care for patients with pressure ulcers. This study aimed to describe changes in stage 1 pressure ulcers in ICU patients during the implementation of nursing care consisting of topical olive oil application, repositioning, and standard skin care. This study was a descriptive case series using an Evidence-Based Nursing Practice approach involving four ICU patients with stage 1 pressure ulcers, total immobility, and decreased level of consciousness. The intervention consisted of topical application of 15 mL of olive oil once daily for seven days, repositioning every two hours, and standard skin care. Wound condition was evaluated using the Pressure Ulcer Scale for Healing (PUSH) on days 1, 4, and 7. During the observation period, all patients showed reductions in the area of erythema and PUSH scores, although the magnitude of change varied among patients. As all patients received the same package of nursing care and no comparison group was included, the specific contribution of olive oil to the observed changes could not be determined. These findings require confirmation through prospective comparative studies with a control group.